The thank you economy - Vaynerchuk, Gary. (New York : Harper Business, 2011)
Gary Vaynerchuk contends that the people and companies harnessing the word-of-mouth power provided by multiplatform media -- those that can shift their outlook and operations to be more customer-aware and fan-friendly -- will pull away from the pack and profit in today's markets.
pt. I. Welcome to the thank you economy : How everything has changed, except human nature ; Erasing lines in the sand ; Why smart people dismiss social media, and why they shouldn't -- pt. II. How to win : From the top: instill the right culture ; The perfect date: traditional media meets social ; I'm on a horse: how Old Spice played ping-pong, then dropped the ball ; Intent: quality versus quantity ; Shock and awe -- pt. III. The thank you economy in action : Avaya: going where the people go ; AJ Bombers: communicating with the community ; Joie de Vivre hotels: caring about the big and little stuff ; Irena Vaksman, DDS: a small practice cuts its teeth on social media ; Hank Heyming: a brief example of well-executed culture and intent -- pt. IV. Sawdust : More thoughts on ... -- pt. V. How to win in the thank you economy, the quick version.
Includes bibliographical references.
Keywords: Customer relations; Social media; Branding (Marketing); Internet marketing; Management